IMPROVING MENTALLY RETARDED STUDENTS’ ABILITY TO WRITE A WORD THROUGH VISUAL, AUDITORY, KINESTHETIC, AND TACTILE (VAKT) METHOD - Q Kamilan; Istiqlaliah Nurul Hidayati; Lestari Sukartiningsih (Pedagogia: Jurnal Ilmiah Pendidikan, 2017)
In this research, VAKT method is chosen to improve the mentally retarded students’ ability to write a word. The subjects of this research are the eighth grade students of SMPLB-C Sejahtera Bogor consisting of four students. The data were collected from October 12th until October 29th, 2015. The method of this research is Classroom Action Research (CAR) which consists of two cycle processes and each cycle consists of three treatments. In the pre-test all of students (100%) belong to poor criteria. After the treatments, the result of the first cycle showed there were two out of four students (50%) got 74 and belong to good criteria. Two other (50%) students got 40 and 54. They still belong to poor criteria. In the second cycle the result showed that one student (25%) got 100 and belongs to excellent criteria; two students (50%) got 80 and 87. They belong to very good criteria. One student (25%) got 74 and belongs to good criteria. The result indicates that VAKT method can improve mentally retarded students’ ability to write a word.